Povezanost med mišično-skeletnimi poškodbami in telesnimi asimetrijami plesalcev - Pavlović, Monika (Šport (Ljubljana), 2020)
Successful execution of dance movements requires highly advanced movement skills such as static and dynamic balance, good flexibility and mobility, muscle strength and power, endurance, coordination and precision in performance. Through training process dancers perform many repetative movements in great range of motion and thus strong forces are transfered especially to low back and lower limbs, therefore musculoskeletal injuries often occur in these body parts. More frequent execution of dance movements to the right side of the body and preference for using one leg to perform primarly balance tasks and the other one to perform dance-specific movements are factors that can lead to the asymmetries and/or musculoskeletal injuries incidence. By reviewing the literature in the field the aim of this paper was to provide key findings on musculoskeletal injuries and body asymmetries in dancers in order to raise awareness of their importance. Studies to date shown a relationship between body asymmetries and musculoskeletal injuries, but it is not yet clear what the cause-effect relationship between these two is and weather some body asymmetries are more common for dancers of certain dance style. For future studies a comprehensive evaluation of movement abilities and physical performance is recommended to enable dancers (and other athletes) more effective and safe sport engagement.
Keywords: dance; dancers; injuries; mišično neravnovesje; muscle imbalance; ples; plesalci; poškodbe; simetrije; symmetries